Release and Disintegration Properties of Poly(Lactic Acid) Films with Allyl Isothiocyanate-Β-Cyclodextrin Inclusion Complexes for Active Food Packaging - Guarda-Moraga, A; Rodriguez-Mercado, F; Galotto-Lopez, M; Muñoz-Shuguli, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study aimed to enhance the properties and compostability of active poly(lactic acid) (PLA) films by incorporating β-cyclodextrin (β-CD) inclusion complexes with allyl isothiocyanate (AITC). Films were prepared using melt extrusion and characterized based on their structural, chemical, morphological, thermal, and barrier properties. These inclusion complexes improved the thermal stability and moisture absorption of films, enhancing disintegration under composting conditions. The release of AITC in the vapor phase was responsive to relative humidity, maintaining the antimicrobial functionality at low values and releasing effectively at higher humidity levels, with a maximum release at 100%. Incorporating 5% and 10% β-CD:AITC complexes accelerated disintegration under composting conditions, reducing the time by 5 days for disintegration compared to pure PLA, achieving up to 90% in 23 days. These results, with a general improvement in functional properties, suggest that PLA films with β-CD:AITC are promising for developing sustainable, biodegradable antimicrobial packaging solutions for food applications. © 2024 by the authors.